Gifted kids or pushy parents? : foreign acquisitions and plant performance in Indonesia - Arnold, Jens Matthias, 1974- 1974- (Policy research working paper, 2005)
"This paper uses micro data from the Indonesian Census of Manufacturing to analyze the causal relationship between foreign ownership and plant productivity. To control for the possible endogeneity of the FDI decision, the difference in differences approach is combined with a matching technique. An advantage of this novel method is the ability to follow the timing of the observed changes in productivity and other aspects of plant performance. The results suggest that foreign ownership leads to significant productivity improvements in the acquired plants. The improvements become visible in the acquisition year and continue in the subsequent periods. After three years, the acquired plants outperform the control group in terms of productivity by 34 percentage points. The data also suggest that the rise in productivity is a result of restructuring, as acquired plants increase their investment outlays, employment, and wages. Foreign ownership also appears to enhance the integration of plants into the global economy through increased exports and imports. "--World Bank web site